2006
DOI: 10.1111/j.1462-5822.2006.00759.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidium parvum infects human cholangiocytes via sphingolipid-enriched membrane microdomains

Abstract: SummaryCryptosporidium parvum attaches to intestinal and biliary epithelial cells via specific molecules on hostcell surface membranes including Gal/GalNAcassociated glycoproteins. Subsequent cellular entry of this parasite depends on host-cell membrane alterations to form a parasitophorous vacuole via activation of phosphatidylinositol 3-kinase (PI-3K)/Cdc42-associated actin remodelling. How C. parvum hijacks these host-cell processes to facilitate its infection of target epithelia is unclear. Using specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…The triggered translocation of ASM from endolysosomal compartments to the host cell surface followed by SM hydrolysis to form ceramide-rich domains seems to play a key role in microbial internalization (Riethmüller et al, 2006). ASM has been associated with infection and host defense against Pseudomonas aeruginosa (Grassmé et al, 2003), Listeria monocytogenes (Utermöhlen et al, 2003) and Cryptosporidium parvum (Nelson et al, 2006). ASM mediates the entry of Neisseria gonorrhoeae into nonphagocytic epithelial (Grassmé et al, 1997) and phagocytic (Hauck et al, 2000) cells via the enrichment of CEACAM receptors for the bacterium in ceramide domains, thus functioning as a portal of microbial entry.…”
Section: Role Of Asm In Microorganism Infectionmentioning
confidence: 99%
“…The triggered translocation of ASM from endolysosomal compartments to the host cell surface followed by SM hydrolysis to form ceramide-rich domains seems to play a key role in microbial internalization (Riethmüller et al, 2006). ASM has been associated with infection and host defense against Pseudomonas aeruginosa (Grassmé et al, 2003), Listeria monocytogenes (Utermöhlen et al, 2003) and Cryptosporidium parvum (Nelson et al, 2006). ASM mediates the entry of Neisseria gonorrhoeae into nonphagocytic epithelial (Grassmé et al, 1997) and phagocytic (Hauck et al, 2000) cells via the enrichment of CEACAM receptors for the bacterium in ceramide domains, thus functioning as a portal of microbial entry.…”
Section: Role Of Asm In Microorganism Infectionmentioning
confidence: 99%
“…While the precise role of myosin IIB during C. parvum invasion is currently unknown, it is reasonable, given the demonstrated roles of myosin II in the regulated exocytosis in chromaffin cells, that myosin IIB may function in the exocytic insertion of transporters and channels that facilitate membrane protrusion events. Additionally, C. parvum invades cholangiocytes via sphingolipid-enriched microdomains (43). Given that myosin IIB localizes to regions of parasite internalization and that myosin II is a component of the cortical membrane cytoskeleton, we propose that inhibition of this molecular motor results in membrane microdomain disorganization and hence inhibits parasitophorous-vacuole formation.…”
Section: Discussionmentioning
confidence: 90%
“…n.a. (Nelson et al 2006) GP40/15 Glycoproteins that have a predicted 60 kDa precursor that is proteolytically cleaved into a 15 and 40 kDa protein probably by a subtilisin-like serine protease (CpSUB1); the GP60 locus is a highly polymorphic cluster and can be divided in two allelic groups Ia-Id (C. hominis), II (C. parvum); GalNAc-specific lectins such as HPA, AIA, and MPA prevent cell attachment and invasion indicating GPs might bind via GalNAc to cells; moreover Nac could reduce binding of the mAb against GP15 but not glucose, mannose or galactose; immunization of mice with mAb against GP15 could reduce oocyst shedding by 67.5%; GP15/GP40 are shed during gliding GP40: predicted N-terminal signal peptide, a polyserine domain, multiple predicted glycosylation sites, a single potential N-glycosylation site GP15: glycosylated, GPI anchor GP15 is localized on the surface of sporozoites and merozoites; GP40 is localized in the apical region whereas GP15 is found on the complete surface; since GP40 does not have a transmembrane domain or GPI anchor it is proposed that GP15 and GP40 form a complex (Tilley et al 1991;Jenkins et al 1993;Cevallos et al 2000a, b;Sestak et al 2002;O'Connor et al 2003O'Connor et al , 2007aWanyiri et al 2009Wanyiri et al , 2007 GP900 Ab against GP900 or subdomains reduced infection of cells in a concentration-dependent manner; GP900 mRNA levels peak at 14-26 h p.i. of cells; comparison of Ab reactivity between C. parvum and C. hominis against GP900 revealed that Ab did not cross-react between the species, indicating that morphological differences of surface molecules might account for species-specific infectivity Mucin-like glycoprotein composed of distal cysteine-rich domains separated by polythreonine domains and a large membrane proximal N-glycosylated core region; deglycosylated protein app.…”
Section: Calcium Is An Important Messengermentioning
confidence: 97%